Pamarsudi Sastra Jawi Bojonegoro: Komunitas Sastra Berbasis Kultur Lokal - M. Shoim; Pana Pramulia (Politeknik Kampar, 2023)
Pamarsudi Sastra Jawi Bojonegoro (PSJB) is one of the most active literary communities in East Java. Until 2023, the age of the studio has reached around 40 years. This qualitative research aims to describe PSJB from an organizational perspective, the profession of the members, the works and literary genres produced, publications, studio activities, and their contribution to the profession and community literacy. Data was collected through interviews and observations, looking at organizational documents, as well as written sources related to PSJB. By using the sociology of literature approach, the data were analyzed, described, and concluded as research results. PSJB can survive because of its tenacity and the existence of central figures in the management. PSJB members are mostly teachers of Javanese language and literature. Organizational activities are more directed to the creative process to produce work. The members' works are published and managed by PSJB. Most of the published works are in the genre of poetry, short stories, and novels. PSJB contributes to the profession and career of its members, most of whom are teachers. It is from these teachers and students that PSJB has contributed to a culture of literacy towards the development of Javanese language and literature as a local culture.